PENERAPAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN COLLABORATION SKILLS SISWA KELAS 5 SEKOLAH DASAR : PENERAPAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN COLLABORATION SKILLS SISWA KELAS 5 SEKOLAH DASAR - Intan Kusuma Wardani; Waskito Aji; Muhammad (STKIP Subang, 2025)
The classroom action research aimed to improve the collaboration skills of fifth-grade students at Krandon Lor 01 Public Elementary School through the application of the Problem-Based Learning (PBL) model. This study had 21 subjects, consisting of 14 male students and 7 female students. The study was conducted in two cycles using Kemmis and McTaggart's spiral design, which included the stages of planning, implementation, observation, and reflection. Data was collected through observation of student collaboration activities, interviews with homeroom teachers, took documentation, subsequently analyzed by descriptive, quantitative, and qualitative. The result of pre-cycle showed that students' collaboration skills were still low, as indicated by their skills in interacting within groups, taking responsibility for completing tasks, and helping each other in group activities, with all students failing to reach the impressive category. After implementing PBL in cycle I and making improvements in cycle II through the formation of group leaders, division of task responsibilities, strengthening of interactions, and the giving of rewards, the percentage of students in the good category increased significantly. At the end of cycle II, the indicators for interacting with the group reached 85%, taking responsibility for completing tasks shows 80%, and helping each other in group activities shows 85%, being said that those percentage exceeding the success criteria of ≥80% for each indicator. Thus, the application of the Problem-Based Learning (PBL) model has been proven to be able to improve the collaboration skills of fifth-grade students at Krandon Lor 01 Public Elementary School.